PENGARUH PENERAPAN PEMBELAJARAN KOOPERATIF TIPE TEAM ASSISTED INDIVIDUALIZATION TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 3 KOTO XI TARUSAN TAHUN PELAJARAN 2013/2014 - Damayanti, Silvia; Harisman, Yulyanti; Rahima, Rahima (Pendidikan Matematika, 2014)
ABSTRACTThis research was background by students mathematical concept comprehension which was low, the students had low abblity just waiting the teacherâs answer and school did not provide enough text book for the eight grade students of SMPN 3 Koto XI Tarusan. The research purpose is to know students mathematical concept comprehension with applying cooperative learning strategy type Team Asssted Individualization better than applying conventional learning of eight grade students in academic year 2013/2014. Â This type of research is experimental research with random sampling as technique interpretation sample and to be population were all students of class VIII SMPN 3 Koto XI TarusanÂ  wich registed in academic year 2013/2014 that amount five classes. The instrument which was used in this research was mathematical concept comprehension test. The test which was essay with test reability = 0,87. Data analysis technique was test t oneside. The result of hyphothesisÂ  = 3,3890 and = 1,6785 because calculate > , so the research hyphothesis was accepted. It can be that students mathematical concept comprehension which applying cooperative learning strategy type Team Assisted Individualizaton better than conventional learning at class VIII SMPN 3 Koto XI Tarusan in academic year 2013/2014.Â